Oxford Research Encyclopedia of Business and Management 2018
DOI: 10.1093/acrefore/9780190224851.013.55
|View full text |Cite
|
Sign up to set email alerts
|

Men, Masculinities, and Gender Relations

Abstract: SummaryEven though gender and gender analysis are still often equated with women, men and masculinities are equally gendered. This applies throughout society, including within organizations. Following 2 pioneering feminist scholarship on work and organizations, explicitly gendered studies on men and masculinities have increased since the 1980s. The need to include the gendered analysis of men and masculinities as part of gender studies of organizations, leadership and management, is now widely recognized at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
0
12
0
1
Order By: Relevance
“…The emergence of postfeminist themes and the recent social and legislative changes across many western countries call for the exploration of the performative dimensions of postfeminist discourses in constructions of femininities and masculinities. We address a critical lack of empirical research on postfeminist masculinities in view of the fact that despite the rise of discursive constructions of men as vulnerable and in crisis, they continue to remain dominant in terms of power, position, leadership, management, pay and resources in most workplaces (Hearn & Collinson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of postfeminist themes and the recent social and legislative changes across many western countries call for the exploration of the performative dimensions of postfeminist discourses in constructions of femininities and masculinities. We address a critical lack of empirical research on postfeminist masculinities in view of the fact that despite the rise of discursive constructions of men as vulnerable and in crisis, they continue to remain dominant in terms of power, position, leadership, management, pay and resources in most workplaces (Hearn & Collinson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of military and war metaphors has been a defining feature of critical leadership and organization studies and highlights how principles of hegemonic masculinity are embedded in organization arrangements (see Collinson and Hearn, 1994; Hearn and Collinson, 2018). This creates gendered work hierarchies and gendered power relations.…”
Section: Resultsmentioning
confidence: 99%
“…A key focus for critical feminist scholars has been to unveil the privileging of masculinist behaviors in leadership theorizing and the dominance of cultural masculinism in studies of organization culture. Critical men's studies have shown how ''hegemonic masculinity'' provides the organizing logic for patriarchy and thus privileges men in both the public and private realm (Collinson and Hearn, 1994;Connell, 1998;Hearn, 2004;Hearn and Collinson, 2018;Messner, 1997). This logic is premised on unequal power relations between men and women, and also those men who do not conform to idealized notions of hegemonic masculinity.…”
Section: A Feminist Poststructuralist Approach To Unravel Tm Assumptionsmentioning
confidence: 99%
“…Seeking to prove that they are powerful and tough ‘real men’, men often compete for and exercise (masculine) power and identity through strategies of dominance and superiority over women and other subordinated men (Collinson & Hearn, 2014). Feeling constantly under pressure to prove their manhood, men are more likely to engage in aggressive and risky behaviour, displays of sexuality, sexual harassment, and to devalue women and those men who do not fit hegemonic criteria (Hearn & Collinson, 2018). Such pressures can be exacerbated by performance systems that pit employees against one another, and workplace cultures that, for example expect long hours working and 24/7 availability (Collinson & Collinson, 2004).…”
Section: Dialectical Approaches To Critical Leadership Studiesmentioning
confidence: 99%